Practices and perceptions of strength and conditioning training in female golf: A cross-sectional survey study of high-level amateur players - Robinson, L.; Murray, A.; Mountjoy, M.; Wells, J.; Coughlan, D.; Glover, D.; Hembrough, R.; Scott, F.; Turner, A.; Bishop, C. (Journal of Sports Sciences, 2024)
This study aims to ascertain an in-depth understanding of current practices and perceptions of S&C training in high-level amateur female golfers. A cross-sectional, explorative survey study was constructed which asked questions relating to four key areas: i) general participant information, ii) current strength and conditioning (S&C) practices, iii) the perceived influence of S&C training on golf performance, and iv) knowledge and awareness of S&C. Results showed that the majority of female players had participated in some form of S&C training in the past, with the majority believing that clubhead speed and carry distance were the primary golfing metrics which could be positively impacted. More specifically, 91-97% of the players "Strongly agreed" or "Agreed" that the key physical characteristics for golf were strength and power for the lower and upper body, and flexibility. Interestingly, 58% of the players believed that S&C training should mimic the movement of the golf swing, which based off current evidence, is not how drive metrics and ultimately shots gained, can be maximised. This survey study provides useful information relating to the practices and perceptions of S&C training in high-level female amateur players and areas where education may be able to further advance player understanding of physical preparation.